Low radiotherapy dose is suitable for brain metastases in SCLC compared with high dose - Xu, Liming; Zhang, Kunning; Han, Haonan; Sun, Han; Yuan, Yajing; Wang, Jun; Zhao, Lujun; Wang, Ping (Frontiers in Oncology, 2023)
contributed equally to the study.【Abstract】 Objective This study was designed to evaluate the suitable radiotherapy dose in SCLC patients with BM. Methods A retrospective analysis was performed among 130 patients on the prognosis of BM of SCLC who were admitted to our hospital from 2010 to 2023. They all received first line chemotherapy. 94 patients of them received TRT after chemotherapy. The Chi square method was used to compare the categorical data. Univariate survival analysis was estimated by Kaplan Meier method and the logrank was used to compare survival curves between groups. A multivariate prognostic analysis was made by the Cox proportional hazard model. The OS and BMRLC of two groups of low dose and high dose were analyzed by propensity score matching (PSM). Results In all the patients, the median followup time was 24.9 months (range 6.30~109.57), the 2-year OS and BMRLC rates were 49.0% and 85%, respectively, and cerebral necrosis occurred in 2 patients. Shorter time interval (months) (≤ 10) (p=0.041), extracranial disease control (p=0.029), and lower DS-GPA (<2) (p=0.006) significantly improved OS in multivariate analysis.After PSM, the 2-year OS of low dose (n=63) was significantly higher than that of high dose (n=63) (P=0.041), while the 2-year BMRLC was not significantly improved (P=0.203). In GPA < 2 subgroup, the OS of SIB group was significantly higher than that of high dose group (p=0.016). In GPA ≥2 subgroup, the difference between OS and high dose group was not observed (p=0.266). There was no significant difference in iLC between GPA<2 and GPA≥2 subgroup (p=0.205 and p=0.027). Conclusions The iLC was improved along with increasing radiotherapy dose, but high dose had inferior iOS compared to low dose, while there were not significantly improving iLC when radiotherapy BED >56Gy. In patients with GPA≥2 subgroup, high dose brought better iLC benefits.